LOCATION SELECTION STUDY FOR BUILDING FISH LANDING PLACE IN DISTRICTS BUKIT BATUBENGKALISDISTRICT RIAUPROVINCE - Muhammad Irwan; Jonny Zain; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The survey was conducted in July 2015, in the village Bukitbatu, Api-api andTenggayun, Bukitbatu district in Riau Province.The purpose of this study was to find thebest location suitable for fish landing building. The method used is the method review /revise the field. Can be seen from the survey data in the technical aspects, fisheries, socioeconomicand infrastructural purpose of the examination of the three villages.The location in the village Tenggayun have advantages, including the opportunity forfishing based on factors such as the number of fishing gear, fishing, the fishing fleet and thenumber of population, which is more than Bukitbatu villages and Api-api. Waters in thevillage Tenggayun fishery potential confounding factors and population factors get thehighest score compared to two other villages, with 55 points and 30 points. The final score ofthe third evaluation village consists of 187 points for Bukitbatu village, 173 points for thevillage burning and 195 points for Tenggayun village. The results of the research using thescoring method showed that the location in the village Tenggayun is the best place to build afish landing sitesKeywords: Selection of location, Fish Landing Place